Colesterolosis vesicular: algunos aspectos de su fisiopatología - Korn B., Owen; Gallegos M., Iván; Hurtado H., Carmen; Guerrero P., Julia (Revista Hospital Clínico Universidad de Chile, 2017)
Gallbladder cholesterolosis is a nosological clinical entity where the central element is the deposit of lipids in immune cells that reside under the gallbladder epithelium. The mechanisms involved in its development are not entirely clear, but they seem to have some resemblances that are observed in the wall of the arteries with atherosclerosis. The lipid-laden cells observed in the gallbladder wall appear to share many of the characteristics of atherosclerosis foam cells, which by means of scavenger receptors have endocited oxidized low-density lipoproteins and accumulate them in their cytoplasm. Foam cells, in themselves, are not dangerous, butin atherosclerosis at least they can become a problem when they are located in vessels and specific anatomic sites. The role they may have in the gallbladder is not known to date. We will review some considerations that seem relevant to us to elucidate if these entities share the same protagonist: macrophages transformed by modified lipids.